2015
DOI: 10.1186/s13601-015-0058-7
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐induced airway hyperresponsiveness and obstruction is related to caveolin‐1 expression in airway smooth muscle in a guinea pig asthma model

Abstract: BackgroundCaveolin-1 is a fundamental signalling scaffold protein involved in contraction; however, the role of caveolin-1 in airway responsiveness remains unclear. We evaluated the relationship between caveolin-1 expression in airway smooth muscle (ASM) and antigen-induced airway responsiveness and obstruction in a guinea pig asthma model.MethodsAirway obstruction in sensitised guinea pigs, induced by antigenic (ovalbumin) challenges administered every 10 days, was measured. Antigen-induced responsiveness to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The lungs express numerous caveolae and high levels of PTRF, which play important roles in pulmonary diseases such as lung cancer and pulmonary hypertension [ 6 , 17 ]. Expression of PTRF in the airway smooth muscle is increased in an OVA-induced asthma model [ 18 ]. Partial loss of PTRF led to a greater AHR and potent type 2 immune responses during challenge phase of OVA-induced asthma model, without influencing the sensitization phase.…”
Section: Discussionmentioning
confidence: 99%
“…The lungs express numerous caveolae and high levels of PTRF, which play important roles in pulmonary diseases such as lung cancer and pulmonary hypertension [ 6 , 17 ]. Expression of PTRF in the airway smooth muscle is increased in an OVA-induced asthma model [ 18 ]. Partial loss of PTRF led to a greater AHR and potent type 2 immune responses during challenge phase of OVA-induced asthma model, without influencing the sensitization phase.…”
Section: Discussionmentioning
confidence: 99%
“…The level of apoptotic caspase-3 protein was found increased in bronchial epithelial cells or lung tissues in asthma [1012]. In contrast, its level was markedly decreased in pulmonary vascular smooth muscle of an asthma model [13]. Apoptosis is also a central and essential process in the resolution of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Animal models of asthma are helpful in the understanding of the disease. Previous studies from our laboratory have shown that the guinea pig allergic asthma model generates airway obstruction and hyperresponsiveness, high ovalbumin‐IgE and ‐IgG1 levels, granulocyte infiltration, increased lung levels of TNF‐α, IL‐4, and IL‐5, remodeling features of asthma such as goblet cell and vascular smooth muscle hyperplasia, and accumulation and alteration of extracellular matrix components [Bazan‐Perkins et al, ; Moreno‐Alvarez et al, ; Ramos‐Ramirez et al, ; Alvarez‐Santos et al, ].…”
mentioning
confidence: 99%